Development of an experimental setup for microflow measurement using interferometry. (October 2020) - Batista, Elsa; Godinho, Isabel; Martins, Rui F.; Mendes, Ricardo; Robarts, João
Abstract: The precise measurement of micro and nanoflow of incompressible liquids (below 1 μL/h) is a complex task due to several factors involved in, namely, evaporation, adsorption and the existence of air bubbles within the system. Nevertheless, the importance of its measurement is undeniable in equipment such as insulin pumps, or medical drug delivery devices for new-born, microchip flow pumps, to mention few. The work herein presented was developed in a partnership between the Volume and Flow Laboratory (LVC) of the Portuguese Institute of Quality (IPQ) and the Department of Mechanical and Industrial Engineering (DEMI) of The New University of Lisbon under the project MeDD II – Metrology for Drug Delivery. It had the main objective of conceiving a new Portuguese standard for the measurement of ultra-low flow using interferometry, with a target uncertainty of 1% ( k = 2). Therefore, the new setup relies on an interferometer made up of a laser unit, two retroreflector cubes, one beam splitter, as well as a flow generator (a Nexus syringe pump) and a computer for data acquisition. Experimental tests on a Flow generator and a Coriolis flow meter were carried out at different flow rates. With the innovative methodology developed during the present research, it was possible to measure flow rates of an incompressible fluid (water) down to 1 μL/h with an uncertainty of 3% ( k = 2). Highlights: New method development for microflow measurement using interferometry. Measurements performed down to 0.001 mL/h with 2.9% uncertainty, k = 2. The new interferometric methodology was internally validated by testing a syringe pump and a BL100 Coriolis flow meter. The interferometer method seems promising to allow obtaining reliable, reproducible, and low uncertainty measurements in the microliter flow domain.